Study of the sensitizing effect of detergents intended for the care of dishes and other products for children (Environment & Health, 2021)
Objective: We evaluated the sensitizing effect of various detergents intended for the care of dishes and other products for children.Materials and methods: The study was carried out in guinea pigs. The sensitization of the animal’s organism was studied in the reaction of degranulation of peripheral blood basophils (after Shelley). Forthestudy, we selected 10% solutions of domestic and foreign products for washing children's dishes ("Alionka", "Karapuz", "Ushastyi Nian", "Frosch Baby") purchased in the supermarkets of Kyiv.Results: In 21 days, the performed study made it possible to establish the development of sensitization of the organism of the animals in the experimental groups exposed to the solutions of the detergents "Alionka", "Karapuz", "Ushasty Nian” for washing children's dishes, although the degree of its manifestation was different. The solution of the detergent "Ushastyi Nian" was shown to possess more pronounced sensitizing properties, as evidenced by the development of weak positive autosensitization and positive sensitization of the organism of the experimental animals.The impact of the detergents for cleaning children's products "Alionka" and "Karapuz"on the animals’ organism leads to the development of mild sensitization, and when using the solution of "Alionka" detergent, a development of the weakly expressed autosensitization of the organism is also observed in the animals.There was no increase in the degranulation of basophilic granulocytes in the presence of both tissue antigen and hapten in the group of animals where the solution of detergent "Frosh Baby" was used, which indicated the absence of auto- and sensitization of the organism of the animals of this group.
Keywords: detergents for washing of children's dishes; sensitization; autosensitization; immediate hypersensitivity